Scenario Planning : The Regulation of the Minister of Education, Culture, Research and Technology Number 41 of 2021 Regarding Recognition of Past Learning in Higher Education Institution - Riswanti, Riyani; Salomo, Roy Valiant (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2024)
Higher Education Gross Participation Rates and Human Development Index must be further improved in higher education. Recognition of Past Learning (RPL) is an important issue that must be paid attention to by the government and stakeholders. In this context, the government needs tools to identify issues and opportunities in RPL development, as well as develop effective strategies to achieve government goals in RPL development. Scenario Planning can be applied to almost any business problem that contains a level of uncertainty. This article will use qualitative methods which aim to describe and draw meaning from various existing planning scenarios. To be able to create Planning scenarios, the method that researchers use is TAIDA, namely Tracking, Analyzing, Imaging, Deciding, Acting. In terms of curriculum flexibility, RPL allows the development of a curriculum that is more flexible and adaptive to labor market needs and individual skill development. As for recognition of Non-formal and Informal Learning, RPL provides recognition of work experience, non-formal training and informal education, which is very important in recognizing skills and knowledge acquired outside formal education. While in cross-sector collaboration, implementing RPL requires strong collaboration between universities, government and industry.